Sonication-induced instant fibrillation and fluorescent labeling of tripeptide fibers1. Issue 66 (19th July 2015) - Pramanik, Apurba; Paikar, Arpita; Haldar, Debasish
<x xml:space="preserve">Abstract</x> A sonication-induced instant fibril formation technique has been used for the co-assembly and fluorescent labeling of peptide nanofibers with organic dyes.